THE ANALYSIS OF STUDENTS’ PERCEPTION ON THE USE OF E-LEARNING AS AN EDUCATIONAL METHOD - Maria Cholifah; Maria Cholifah; Aulia Nur Hijriyanti; Maria Purnawati (JURNAL ILMIAH BAHASA DAN SASTRA, 2022)
The goal of this study was to examine the students’ perceptions on the use of E-learning as an educational method, moreover to identify the benefit and challenges of using E-learning as an educational method in the English Education Department 2019 intake at Universitas PGRI Kanjuruhan Malang. In this research, the researchers used the qualitative method. The subject of this research was 40 students of the English Education Department 2019 intake. The data were collected through questionnaires to 40 students and interviewed by ten participants. The data were analyzed by using data reduction, data display, and drawing conclusions/verification. The finding showed that of the 40 students who filled out the questionnaire, 7 students stated strongly agree and 31 students agreed that they had experience using E-learning. This means that most of the participants who have filled out the questionnaire have experience using E-learning and there are several supporting facilities for using E-learning. The students felt that E-learning is useful and interesting to use, E-learning can also add new knowledge about technology that has never been obtained before, etc. Furthermore, the problems faced by the students in using E Learning were limited availability of internet access, the students felt bored, students' learning motivation was reduced, and students found difficulty to understand the lessons.